Household flood preparedness and associated factors in the flood-prone community of Dembia district, Amhara National Regional State, northwest Ethiopia - Ashenefe B; Wubshet M; Shimeka A (Dove Medical Press, 2017)
Baye Ashenefe,1 Mamo Wubshet,2 Alemayehu Shimeka3 1North Gondar Zonal Health Department, 2Department of Public Health, St Paul Millineum Medical College, Addis Ababa, 3Department of Epidemiology and Bio-Statistics, Institute of Public Health, University of Gondar, Gondar, Ethiopia Background: Flood preparedness empowers the community to respond effectively to related hazards. However, there was no research done in the country concerning household flood preparedness. Therefore, the aim of this study was to assess household flood preparedness and associated factors in the flood-prone community of Dembia district, northwest Ethiopia.Methods: A community-based cross-sectional study was conducted from March to April 2014 in the Dembia district. A two-stage sampling technique was used. The study was conducted using 806 flood-prone participants. An interviewer-administered questionnaire was used to collect data. The collected data were entered using Epi info version 3.5.1 and transported into SPSS version 16 for further analysis. Descriptive and analytic statistics were computed. Variables having association with the outcome variable were reported using odds ratio with 95% confidence interval (CI). Model fitness was checked by Hosmer and Lemeshew chi-square test.Results: Household flood preparedness was found to be 24.4%. The age group of ≥ 46 years (adjusted odds ratio [AOR]=2.62; 95% CI: 1.12, 6.00) above, monthly household income >893 Ethiopian Birr, (AOR=6.72; 95% CI: 2.2 7, 19.88) attending primary level education (AOR=22.08; 95% CI: 8.16, 59.74), warning system in household (AOR=5.41; 95% CI: 2.38, 12.32), knowledge of flood prevention, (AOR=2.52; 95% CI: 1.43, 5.57) were positively associated with household flood preparedness.Conclusion and recommendation: This study has demonstrated that household flood preparedness was found to be low in the study area. Household flood preparedness was significantly associated with the older age group, attending primary level education, having a higher monthly income, receive household level warning messages, having knowledge on preparedness, prior exposure to a flood, and length of flood >6 days. Strengthening household flood preparedness in advance is important in order to prevent flood and its related consequences. Keywords: household, flood preparedness, flood, Ethiopia